LAYANAN MOBILE SIMARI TERHADAP KEPUASAN ANGGOTA DI KOPERASI JASA SYARIAH MAMBAUL RIZKI INVESTAMA, CABANG KARAWANG, JAWA BARAT - Sidik, Syahrial; Wahyuari, Wahyuari; Sapolo, Supriyadi; Kurniartha, Alvernia (Premium Insurance Business Journal, 2023)
This study evaluates member satisfaction with Mobile SIMARI services at Mambaul Rizki Investama Sharia Services Cooperative, Karawang Branch, West Java. In the era of digitalization, Sharia Services cooperatives are adopting technology to simplify financial transactions. The SIMARI Mobile service was launched to provide easy transactions for cooperative members through features such as cardless cash withdrawals, credit top-ups, and bill payments. Using the Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI) methods, this study measures member satisfaction with Mobile SIMARI services. IPA results show that KJ2 and KJ6 services need to be improved, while other services are satisfactory. The CSI results show that the member satisfaction level reached 83.95%, indicating that this service is very satisfying. This research makes a significant contribution to the development of marketing strategies for Islamic services cooperatives, emphasizing the importance of digital technology integration in increasing member satisfaction and loyalty. The findings can serve as a reference for other cooperatives looking to adopt similar technologies to improve their service quality. Thus, Mambaul Rizki Investama Islamic Services Cooperative can be a pioneer in innovative and socially responsible business practices.